Lipid Nanoparticles in Lung Cancer Therapy - Hossein Omidian; Erma J. Gill; Luigi X. Cubeddu (MDPI AG, 2024)
This manuscript explores the use of lipid nanoparticles (LNPs) in addressing the pivotal challenges of lung cancer treatment, including drug delivery inefficacy and multi-drug resistance. LNPs have significantly advanced targeted therapy by improving the precision and reducing the systemic toxicity of chemotherapeutics such as doxorubicin and paclitaxel. This manuscript details the design and benefits of various LNP systems, including solid lipid-polymer hybrids, which offer controlled release and enhanced drug encapsulation. Despite achievements in reducing tumor size and enhancing survival, challenges such as manufacturing complexity, biocompatibility, and variable clinical outcomes persist. Future directions are aimed at refining targeting capabilities, expanding combinatorial therapies, and integrating advanced manufacturing techniques to tailor treatments to individual patient profiles, thus promising to transform lung cancer therapy through interdisciplinary collaboration and regulatory innovation.